Chandra Probes the X-Ray Variability of M51 ULX-7: Evidence of Propeller Transition and X-Ray Dips on Orbital Periods - Vasilopoulos, Georgios; Koliopanos, Filippos; Haberl, Frank; Treiber, Helena; Brightman, Murray; Earnshaw, Hannah P.; Gúrpide, Andrés (IOP, 2021)
We report on the temporal properties of the ultraluminous X-ray (ULX) pulsar M51 ULX-7 inferred from the analysis of the 2018-2020 Swift/X-ray Telescope monitoring data and archival Chandra data obtained over a period of 33 days in 2012. We find an extended low flux state, which might be indicative of propeller transition, lending further support to the interpretation that the neutron star is rotating near equilibrium. Alternatively, this off-state could be related to a variable superorbital period. Moreover, we report the discovery of periodic dips in the X-ray light curve that are associated with the binary orbital period. The presence of the dips implies a configuration where the orbital plane of the binary is closer to an edge-on orientation, and thus demonstrates that favorable geometries are not necessary in order to observe ULX pulsars. These characteristics are similar to those seen in prototypical X-ray pulsars such as Her X-1 and SMC X-1 or other ULX pulsars such as NGC 5907 ULX1.
Keywords: 1108; 1306; 733; Astrophysics - High Energy Astrophysical Phenomena; High mass x-ray binary stars; Neutron stars; Pulsars